Association of the IL‐10 receptor A536G (S138G) loss‐of‐function variant with multiple sclerosis in Tunisian patients. Issue 5 (22nd February 2017) - Ben Fredj, Nadia; Aissi, Mouna; Ben Selma, Walid; Mahmoud, Imen; Nefzi, Faten; Frih‐Ayed, Mahbouba; Boukadida, Jalel; Aouni, Mahjoub
Abstract : Interleukin‐10 (IL‐10), a potent anti‐inflammatory T‐cell cytokine, has been shown to be a regulatory cytokine that is associated with disease remission in multiple sclerosis (MS) and exerts its activity through its cognate cell surface receptor complex, IL‐10 receptor 1 (IL‐10R1) and IL‐10R2. The purpose of this study was to investigate the IL‐10R1 S138G loss‐of‐function polymorphism (A536G: rs3135932) for possible influence on susceptibility and outcome of MS in Tunisian patients. A total of 103 Tunisian MS patients and 160 control subjects were studied. Genomic DNA samples were extracted from leukocytes and used to investigate S138G polymorphism in IL‐10R1 gene by multiplex allele‐specific polymerase chain reaction. Associations between G allele [odds ratio (OR) = 5.57; 95% confidence intervals (CI) = 3.26–9.54; p = 10 −7 ], GG genotypes [OR = 10.41; 95% CI = 2.28–47.58; p = 0.0007] and AG genotype [OR = 4.14; 95% CI = 2.16–7.93; p = 0.000016] with the risk development of MS were found. In contrast, the AA genotype seemed to be associated with protection against MS [OR = 0.17; 95% CI = 0.09–0.30; p = 10 −7 ]. No association was found between S138G SNP and clinical features or disease activity of MS patients. In conclusion, our results suggest that S138G loss‐of‐function polymorphism of the IL‐10R1 may be important risk factor in increasing susceptibility to MS.